GAMBARAN TINGKAT RISIKO STROKE PADA MASYARAKAT USIA PRODUKTIF - Nadiatul Khairiyah; Wasisto Utomo; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Stroke is a disease with the most major neurological disability that strikes suddenly for the affected patient. The incidence of stroke continues to increase, including with age. Stroke risk factors consist of modifiable and non-modifiable. Stroke prevention can be started from an early age and the best age for stroke risk prevention is productive age. This study aims to describe the level of stroke risk in people of productive age. This study uses a descriptive design with a cross sectional approach. The research sample was 100 respondents who were taken based on the inclusion criteria using consecutive sampling technique. The analysis used was univariate analysis consisting of age, gender, education level, occupation and stroke risk. The results showed that most respondents had a moderate risk of stroke as many as 38% of respondents. The conclusion obtained in this study is that the highest risk of stroke is that respondents have moderate stroke risk as many as 38% of respondents. Low risk was obtained as much as 37% and the least risk was respondents who had a high risk of stroke, namely as much as 25%. It is recommended for further researchers to narrow the characteristics of respondents and examine the behavior of preventing stroke risk in people who have degenerative diseases.Keywords: Productive age; Risk of stroke; Stroke prevention.